THE EFFORT SCHIZOPHRENIC CHARACTER IN “A BEAUTIFUL MIND” NOVEL BY SYLVIA NASAR - Sri Mariyani Laiya; Dahlia Husain (Universitas Muhammadiyah Gorontalo, 2022)
AbstractThe problem in this research is how the condition of the main character of a mathematical sicentist who suffers from schizophrenia and the efforts made to recover from this illness in the novel A Beautiful Mind. This research focus to Maslow theory about hierarchy of needs in Sylvia Nasar Novel, titled A Beautiful Mind. The method that used in this research is descriptive qualitative method. The data that used in this research is documentation technique. The researcher used Maslow’s theory to analysis the novel. Depend on the analysis, it can be concluded that A Beautiful Mind novel is describes how the condition of mathematical scientist who are battling schizophrenia.Keywords: Hierarchy of Needs, Sylvia Nasar, A Beautiful Mind, Schizophrenia